2023
DOI: 10.1083/jcb.202209094
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale structural organization and stoichiometry of the budding yeast kinetochore

Abstract: Proper chromosome segregation is crucial for cell division. In eukaryotes, this is achieved by the kinetochore, an evolutionarily conserved multiprotein complex that physically links the DNA to spindle microtubules and takes an active role in monitoring and correcting erroneous spindle–chromosome attachments. Our mechanistic understanding of these functions and how they ensure an error-free outcome of mitosis is still limited, partly because we lack a complete understanding of the kinetochore structure in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 99 publications
6
12
0
Order By: Relevance
“…Additional CENP-A molecules may serve to maintain CENP-A nucleosomes at point centromeres ( 75 ), potentially also involving Ndc10 that directly recruits the CENP-A chaperone Scm3 involved in the deposition of CENP-A during S phase ( 56 , 76 ). Discrepancies between the three studies, finding two CENP-A histones at centromeres ( 69 , 70 , 73 ) and the two studies reporting four to five CENP-A molecules ( 57 , 72 ), might result from errors associated with methods used to calibrate CENP-A fluorescence signals with in vitro or exogenous green fluorescent protein (GFP) standards, the photophysical properties of GFP, the background correction, and the tendency of C-terminally GFP-tagged CENP-A to bind DNA nonspecifically ( 69 , 70 ). In vivo fluorescence studies also revealed higher levels of subunits of the COMA/CENP-OPQU+ subcomplex ( 57 , 66 ), a finding we attribute to the additional interactions between CENP-QU and CENP-A END , as discussed below.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Additional CENP-A molecules may serve to maintain CENP-A nucleosomes at point centromeres ( 75 ), potentially also involving Ndc10 that directly recruits the CENP-A chaperone Scm3 involved in the deposition of CENP-A during S phase ( 56 , 76 ). Discrepancies between the three studies, finding two CENP-A histones at centromeres ( 69 , 70 , 73 ) and the two studies reporting four to five CENP-A molecules ( 57 , 72 ), might result from errors associated with methods used to calibrate CENP-A fluorescence signals with in vitro or exogenous green fluorescent protein (GFP) standards, the photophysical properties of GFP, the background correction, and the tendency of C-terminally GFP-tagged CENP-A to bind DNA nonspecifically ( 69 , 70 ). In vivo fluorescence studies also revealed higher levels of subunits of the COMA/CENP-OPQU+ subcomplex ( 57 , 66 ), a finding we attribute to the additional interactions between CENP-QU and CENP-A END , as discussed below.…”
Section: Discussionmentioning
confidence: 91%
“…An earlier in vivo study reported a mean of five CENP-A subunits associated with budding yeast centromeres ( 72 ). Recently, a single-molecule localization microscopy study estimated that four CENP-A molecules were present at individual budding yeast kinetochore complexes in situ ( 57 ). Because inhibiting protein synthesis, which specifically decreases non-centromeric CENP-A, reduced CENP-A protein copy number by 30 to 40%, this study would also be consistent with approximately one CENP-A Nuc directly associated with the point centromere.…”
Section: Discussionmentioning
confidence: 99%
“…The SMLM study on the S. cerevisiae KT ( Cieslinski et al, 2023 ), carried out in parallel to our work, is a perfect complement. Comparing the phylogenetically quite distant yeasts, the data consistently show that KTs generally possess similar architecture despite S. cerevisiae maintaining a point centromere and S. pombe a regional structure ( Tables S4 and S5 ).…”
Section: Resultsmentioning
confidence: 96%
“…This is inverted for S. cerevisiae ( Bock et al, 2012 ; De Wulf et al, 2003 ; Giaever et al, 2002 ; Kim et al, 2010 ; Meeks-Wagner et al, 1986 ; Schleiffer et al, 2012 ). This organismal difference is also reflected in protein copy numbers as Mif2 (cnp3 CENP-C ) is more abundant than Cnn1 (cnp20 CENP-T ) in S. cerevisiae , chicken, and humans ( Cieslinski et al, 2023 ; Johnston et al, 2010 ; Suzuki et al, 2015 ). For the COMAc, fta7 CENP-Q (Ame1) and mis17 (Okp1) are essential for both yeasts ( Hayles et al, 2013 ; Kim et al, 2010 ) and deletions of fta2 CENP-P and mal2 CENP-O are non-viable in S. pombe .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation